2016
DOI: 10.1007/s11367-016-1248-9
|View full text |Cite
|
Sign up to set email alerts
|

LCA and decision making: when and how to use consequential LCA; 62nd LCA forum, Swiss Federal Institute of Technology, Zürich, 9 September 2016

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…These approaches all come with a number of simplifications given the difficulty of the task at hand (Majeau-Bettez et al 2018;. For example, economic models, which are often associated with CLCA and are behind most of the energy scenarios used in this work, face different shortcomings, including insufficient representation of future technologies, lack of transparency, difficulty to evaluate uncertainty, reliance on perfect competition assumption and the inability to capture certain non-economic elements (Marvuglia et al 2013;Zamagni 2013;Menten et al 2015;Wikipedia 2016;Frischknecht et al 2017). The consequential system model of the ecoinvent database was built to reflect long-term consequences of small-scale decisions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These approaches all come with a number of simplifications given the difficulty of the task at hand (Majeau-Bettez et al 2018;. For example, economic models, which are often associated with CLCA and are behind most of the energy scenarios used in this work, face different shortcomings, including insufficient representation of future technologies, lack of transparency, difficulty to evaluate uncertainty, reliance on perfect competition assumption and the inability to capture certain non-economic elements (Marvuglia et al 2013;Zamagni 2013;Menten et al 2015;Wikipedia 2016;Frischknecht et al 2017). The consequential system model of the ecoinvent database was built to reflect long-term consequences of small-scale decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution, which is used systematically to handle multifunctionality in CLCA, relies on one-to-one ratios that are revealed to be inaccurate (Chalmers et al 2015;Vadenbo et al 2017). This issue stems from the linearity assumption generally applied in the field of LCA and could be lifted with the introduction of elasticities to characterize the substitution and supply links between products (Frischknecht et al 2017;Yang and Heijungs 2018b). Nevertheless, it remains unclear how to implement this option at the scale of an LCI database.…”
Section: Discussionmentioning
confidence: 99%
“…Consequential LCA should be more than the use of marginal mixes, as pointed out in the 62 • LCA conference [68]. However, in the LCA of EV, it emerges that the difference between ALCA and CLCA is often identified with the difference between average and marginal electricity mixes, and the terms are sometimes used as synonyms.…”
Section: Clca In Electric Mobilitymentioning
confidence: 99%
“…A survey by Zanghelini et al [48] found that multicriteria decision analysis is typically used in three different stages in an LCA: life cycle impact assessment (e.g., weighting), life cycle inventory, and goal and scope definition. Decisions can also be made for different systems of interest, for example, the neighbourhood level [49], building level [39,40], component level [50], and material level [51,52]. A general challenge is to balance precision with timeliness, or to know "when 'good enough' is best" as formulated by Bala et al [53].…”
Section: Procedural Methodsmentioning
confidence: 99%